Clinical and psychological aspects of true arterial hypertension and white coat hypertension. (25th November 2020) - Legkonogov, A; Sokolovskaya, E
Abstract: Purpose: To compare the clinical and psychological features, as well as echocardiographic and ambulatory blood pressure monitoring (ABPM) data in patients with true arterial hypertension (AH) and white coat hypertension (WCH). Methods: Were studied 154 subjects (58 men and 96 women, average age 52.9±0.7 years) with increased office blood pressure. The control group consisted of 31 healthy individuals (12 men and 19 women, average age 51.5±2.4 years). All individuals underwent ABPM, Doppler echocardiography, and psychological status studies using the MMPI and Spielberger tests. Results: ABPM confirmed the presence of AH in 127 (47 men and 80 women, average age 53.3±0.8 years) of 154 examined patients. 27 patients (17.5%) were diagnosed with WCH - 11 men and 16 women, the average age of 50.8±1.4 years. Among healthy individuals, dippers prevailed, while among AH patients the proportion of dippers was significantly lower (p<0.001) compared with the control group, and a larger number of non-dippers, over-dippers and night-peakers was noted (p<0.01). The distribution of patients with WCH by the type of the daily profile of blood pressure (BP) did not significantly differ from that in healthy individuals (p>0.05). Patients with AH compared with healthy patients had higher average values of the left ventricular (LV) posterior wall as well as interventricular septum thickness, left atrium diameter, and LV myocardial mass index. We found no signs of LV hypertrophy in WCH patients and healthy individuals. The correlation analysis confirmed a reliable relationship between most echocardiographic parameters and ABPM in AH patients (p<0.05). The results of the MMPI and Spielberger tests revealed higher levels of reactive and personal anxiety in patients with AH compared with healthy individuals. Patients with WCH were characterized by disharmonious personality profiles and, in comparison with the control group, more pronounced hypochondriac, hysteroid, and psychasthenic features. Compared with AH patients, subjects with WCH were characterized by less pronounced depression, isolation, rigidity of anxious affect, as well as a more pronounced demonstrative behavior. Conclusions: In people with AH patients the structural and functional characteristics of the heart there correlate with the ABPM results. In contrast, echocardiographic findings in individuals with WCH do not significantly differ from those in healthy subjects. Individuals with WCH have more pronounced hypochondriacs, anxious-suspicious and hysteroid personality traits, while for patients with AH depression, isolation, and rigidity of anxious affect are more common. Funding Acknowledgement: Type of funding source: None